Hydroxyapatite Coating of Titanium Implants Using Hydroprocessing and Evaluation of Their Osteoconductivity - Kensuke Kuroda; Masazumi Okido (Bioinorganic Chemistry and Applications)
Many techniques for the surface modification of titanium and its alloys have been proposed from the viewpoint of improving bioactivity. This paper contains an overview of surface treatment methods, including coating with hydroxyapatite (HAp), an osteoconductive compound. There are two types of coating methods: pyroprocessing and hydroprocessing. In this paper, hydroprocessing for coating on the titanium substrate with HAp, carbonate apatite (CO3–Ap), a CO3–Ap/CaCO3 composite, HAp/collagen, and a HAp/gelatin composite is outlined. Moreover, evaluation by implantation of surface-modified samples in rat tibiae is described.